Salesperson Training as an Effective Tool to Increase SME Sales - Djakasaputra, Arifin; Christinio, Elizabeth; Jayanti, Yunia Arinda (CV. Proaksara Global Transeduka, 2024)
As a salesperson / personal selling / salesperson is the key to success in generating the buying process. Personal selling is an effective tool to build preferences, beliefs, and purchase actions. For this reason, business owners must increase their expertise which can be achieved through salles training in using adequate facilities. As a seller, you must master every product or service that the company sells. The purpose of the activity is to help business owners have a stock of knowledge about salespeople, so that business owners can increase sales of the products produced. The partner chosen in the PKM activity is engaged in a culinary business domiciled in Jambi. The method offered to partners is training/socialization which includes an introduction to salespeople, characteristics, forms, principles and goals and benefits. Presented in the form of PPT and conducted online. The results of the activity show that partners can optimize personal selling skills in offering products to end consumers, as evidenced by the results of the evaluation of the answers to the questionnaires given to partners showing 100% can understand the material presented.